The answer is 0.
The expression in algebraic form is :
We know subtracting a term from its equivalent term will be 0.
You can only solve this by having the same base on each side. So to change 1/27, you can use 3^-3, which is then multiplied through. So the equation is:
4x-5=-3(2x+10)
4x-5=-6x-30
10x=-25
x=-2.5
I would guess 61 in my school we only do things like this x4 - 5 x times four minus five so I don’t know if that’s right but that would be my guess if that isn’t right it would be 62 times 2